Wyzwania sektora energii w kontekście transformacji energetycznej - Cop, Kacper (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article aims to answer whether the current state of the Polish energy system may lead to its crisis and in turn threaten the country’s energy security. This assumption was verified with the use of statistical data analysis and a review of literature. The study indicates several negative phenomena affecting the Polish energy sector. They include the lack of far-reaching reforms in the Polish energy market and negative external effects that may lead to a crisis.
Keywords: energy security; renewable energy sources (RES); reduction of carbon dioxide emissions; energy policy of the EU and Poland; EU Emissions Trading System (EU ETS)